2020
DOI: 10.1101/2020.12.14.422739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decomposing the sources of SARS-CoV-2 fitness variation in the United States

Abstract: The fitness of a pathogen is composite phenotype determined by many different factors influencing growth rates both within and between hosts. Determining what factors shape fitness at the host population-level is especially challenging because both intrinsic factors like pathogen genetics and extrinsic factors such as host behaviour influence between-host transmission potential. These challenges have been highlighted by controversy surrounding the population-level fitness effects of mutations in the SARS-CoV-2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Interestingly, that particular mutation is not worrying for antibody‐based therapeutics and vaccines since it actually increases the susceptibility to neutralisation 60,61 . D614G first established in countries where transmission rates at the beginning of the pandemic were higher, 23,62 leading to huge expansions. The P323L mutation in the RNA‐dependent RNA polymerase (often referred as NSP12b:P314L) accompanies the D614G Spike mutation in most of the analysed sequences (MR = 0.994) 19…”
Section: Spike Protein Mutations Detected In Currently Circulating Strainsmentioning
confidence: 99%
“…Interestingly, that particular mutation is not worrying for antibody‐based therapeutics and vaccines since it actually increases the susceptibility to neutralisation 60,61 . D614G first established in countries where transmission rates at the beginning of the pandemic were higher, 23,62 leading to huge expansions. The P323L mutation in the RNA‐dependent RNA polymerase (often referred as NSP12b:P314L) accompanies the D614G Spike mutation in most of the analysed sequences (MR = 0.994) 19…”
Section: Spike Protein Mutations Detected In Currently Circulating Strainsmentioning
confidence: 99%
“…Why mutations R203K and G204R have such frequencies in most of the continents, why in North America, those mutations were not so successful and why currently Europe is dominated by OTU_2 are open questions. Some studies showed that at the moment, there are not mutations that significative increase the fitness of the SARS-CoV-2 (Kepler et al, 2020;van Dorp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%